Studi Empiris Pengambilan Keputusan Heuristik Pasar Modal Indonesia Studi Kasus Investor di Kota Malang - Audito Aji Anugrah; Daniel Sugama Stephanus; Putu Indrajaya Lembut (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2023)
The purpose of this research is to investigate the effect of Anchoring, Overconfidence, Herding Bias, Hindsight Bias and Representativeness on heuristic decision making. The responden for this study are Investor Indonesia Stock Exchange which scope in Malang. The result shows that Anchoring, Overconfidence, Herding Bias, Hindsight Bias doesn’t have impact on heuristic decision making Malang Investor. But Representativeness have significant effect on heuristic decision making Malang Investor. The results of this research test show that Malang Investor has several heuristic variables that do not influence decision making by investors in other factors. Other dimensional factors impact to be differences in the results of empirical evidence are in terms of Culture and Knowledge Sharing. In terms of Culture,each district has different individual behavior characteristics. Differences in these characteristics lead to a paradox towards the characteristics of behavior that depends in terms of context and culture. Knowledge Sharing as a factor also has a role in influencing individual characteristics in making decisions. Each individual has diversity and different levels for knowledge sharing dimensions depending on the individual's ability to interpret a knowledge obtained.